Exploring Pedagogies that teachers draw on to teach reading in Grade 10 English First Additional Language inclusive classes - Ndlovu, Sheillah (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa)
This qualitative, interpretive study explored the pedagogies teachers drew on to teach reading in Grade 10 English First Additional Language inclusive classes. Over the years, children with learning difficulties have been excluded from formal learning and placed in special schools. However, the transformation through inclusive education allows learners with learning difficulties to be enrolled in mainstream schools. Unfortunately, mainstream teachers were not trained to address learning difficulties. It is for this reason that this study explored the pedagogies that teachers drew on to teach reading through an exploratory case study of five teachers and grade 10 learners, noting responses of learners with learning difficulties at one school in John Taolo Gaetsewe (JTG) district in Northern Cape. This study was guided by Sen's capability approach. Semi-structured interviews, focus group interviews, and non-participant observations were used to collect data on the pedagogies teachers draw on to teach reading in inclusive classes and learners' views on how they want to be taught reading. The collected data was analysed through a thematic data analysis approach with the hope that the findings will help to develop and enrich teachers in teaching reading in inclusive classes to engage all learners. Findings revealed that the participating teachers drew from various pedagogies such as Reading to Learn, Establishing, Maintaining, and Consolidating, and Question-Answer- Relationship. The similarities among these pedagogies are their repetitive nature and that they provide maximum opportunities for learners with various needs, abilities, and challenges to succeed. The teachers' self-developed strategies were influenced by the need to promote Ubuntu and collaborative learning. Knowing learners and their weaknesses was key to developing strategies. Teachers can draw from various pedagogies to teach reading in an inclusive class. This study recommends using multimodal texts, compulsory inclusive education during initial teacher education, and combined use of pedagogies.
Keywords: English language-- Study and teaching Foreign speakers; Inclusive education -- South Africa Northern Cape; Capabilities approach (Social sciences); Reading (Secondary); Reading comprehension; Learning disabilities